A new species of Campsurus Eaton, 1868 (Ephemeroptera: Polymitarcyidae) from the Doce River Basin, Brazil - Pantoja, Gabriel M.; Viana, Ana D. L.; Salles, Frederico F. (Zootaxa, 2023)
The male imago of Campsurus mirim sp. nov., an integrant of the C. major species group, is described based on material from a lake at the Rio Doce basin, Southeastern Brazil. It can be distinguished from other species of the group by the following combination of characteristics: small to medium size (body 7.3 mm, forewings 6.1 mm); blackish pigments on dorsum of head widely and strongly marked in fresh material; abdominal color pattern with pale transverse dashes on terga III–VII; posterior margin of sternum IX triangular at middle; pedestals flat with inner margin broadly rounded and with both posterolateral corners (inner and outer) approximately of the same length, both acute; penes relatively wide and large, ventrally curved on apical ½ and with apex of main lobe slightly twisted.